2009
DOI: 10.1007/s00423-009-0575-8
|View full text |Cite
|
Sign up to set email alerts
|

Variability of surgical knot tying techniques: do we need to standardize?

Abstract: This explorative study detected a high variability of knot tying techniques among German surgeons. In the absence of any evidence of the superiority of one particular technique, continuing education should focus on the quality of each single knot and perfect the details of the technique used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Obviously, we were unable to apply constant peak tension to a knot, which is a clear limitation of our study but in accordance with findings of Butz et al [9]. Obviously not only between surgeons it seems to be impossible to standardize suture tension in hand-knotted sutures [10] but also the same surgeon underlies a great variability of suture tension since all sutures were performed by the same person. Therefore, it might be favourable to develop a suture device which provides standardized suture tension.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Obviously, we were unable to apply constant peak tension to a knot, which is a clear limitation of our study but in accordance with findings of Butz et al [9]. Obviously not only between surgeons it seems to be impossible to standardize suture tension in hand-knotted sutures [10] but also the same surgeon underlies a great variability of suture tension since all sutures were performed by the same person. Therefore, it might be favourable to develop a suture device which provides standardized suture tension.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, several experimental studies had demonstrated, that any high suture tension additionally has a negative influence on the quality of wound healing by inducing ischemia, oedema and tissue necrosis [6-8]. Despite, even today we are not able to control the tensile strength that is applied when knotting surgical sutures [9,10]. A correctly performed suture usually is related vaguely to "clinical experience" of the surgeon [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, surgeons would use more than 3 throws to fix a surgical knot or at least commonly change the direction of the loop and the thread end under tension to secure the knot. 1 Obviously, 1 knot configuration does not provide a general rule for knot safety of all other knots but at least describes the knot safety of 2 suture materials regarding 1 selected knot configuration under comparable conditions. The knot has been selected based on the research results indicating that some knots would slip whereas others may rather break.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the perfect knotting technique is still being discussed and surgical training programs are still being developed. [1][2][3] Therefore, a method is urgently needed which could determine objectively the knot safety of certain knot types in a surgical operation field.…”
mentioning
confidence: 99%